Application of morphological criteria for definition of management approach for child with ulcerative colitis - E. N. Fedulova; P. P. Potekhin; O. V. Shumilova; N. Yu. Shirokova; O. V. Fedorova; O. A. Tutina; G. V. Medyantseva; A. R. Bogomolov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of clinical case presentation. To show importance of interpreting of morphological data not only for statement of diagnosis and evaluation of activity of inflammatory process, but also for revealing morphological changes testifying aggressive course of disease, and to demonstrate efficacy of anticytokine therapy in achievement of histological remission.Features of the case. Definition of indications for infliximab prescription, based on morphological data is submitted, as well as efficacy of this agent in achievement of histological remission in a child with hormonedependent ulcerative colitis. Morphological criteria of aggressive variant of pathomorphism of ulcerative colitis (ileal spread with development of the structural features typical for mucosa of the large intestine, and phenomenon of small-intestinal metaplasia in distal parts of the large intestine) can serve as one of indications to prescription of infliximab.Conclusion. Morphological criteria of aggressive variant of pathomorphism of ulcerative colitis allowed well-timed prescribtion of anticytokine treatment for a girl with ulcerative colitis, and efficacy was confirmed by achievement of histological remission.